2016
DOI: 10.3892/or.2016.5310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of casein kinase 2 prevents growth of human osteosarcoma

Abstract: High-dose chemotherapy and surgical treatment have improved the prognosis of osteosarcoma. However, more than 20% of patients with osteosarcoma still have a poor prognosis. We investigated the expression and function of casein kinase 2 (CK2) in osteosarcoma growth. We then examined the effects of CX-4945, a CK2 inhibitor, on osteosarcoma growth in vitro and in vivo to apply our findings to the clinical setting. We examined the expression of CK2α and CK2β by western blot analysis, and performed WST-1 assays usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
19
2
Order By: Relevance
“…Kinases catalyze the transfer of phosphate groups from high-energy, phosphate-donating molecules to specific substrates. Takahashi et al [27] used siRNA and the small molecule inhibitor CX-4945 to show that upregulation of casein kinase 2 (CK2) was important for the growth of human osteosarcoma cells. Zhu et al [28] reported that the checkpoint kinase inhibitor AZD7762 promoted apoptosis and mitotic catastrophe in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kinases catalyze the transfer of phosphate groups from high-energy, phosphate-donating molecules to specific substrates. Takahashi et al [27] used siRNA and the small molecule inhibitor CX-4945 to show that upregulation of casein kinase 2 (CK2) was important for the growth of human osteosarcoma cells. Zhu et al [28] reported that the checkpoint kinase inhibitor AZD7762 promoted apoptosis and mitotic catastrophe in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described (18). Cells were lysed using NP40 buffer, which contained 0.5% NP-40, 10 mM Tris-HCl (pH 7.4), 150 mM NaCl, 3 mM phenylmethylsulfonyl fluoride (Wako Pure Chemical Industries Co., Ltd., Kanagawa, Japan), 5 mg/ml aprotinin (Sigma-Aldrich; Merck KGaA), 2 mM sodium orthovanadate (Wako Pure Chemical Industries) and 5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Takahashi et al found overexpression of CK2α and CK2β protein in human osteosarcoma cell lines when compared to normal cells [127]. Furthermore, knockdown of either CK2α or CK2β with siRNA or incubation with CX-4945 led to prevention of osteosarcoma cell proliferation.…”
Section: Sarcomamentioning
confidence: 99%